Sarcopenia and the syndrome of frailty - Ajay Kumar Gupta; Siddhartha Mishra (SpringerOpen, 2016)
Sarcopenia is the process of loss of body mass, specifically the musculoskeletal tissue, with age, which ultimately leads to a syndrome of clinical entity poorly defined as frailty. It is probably as old as humanity itself. Functionally, frailty is described as a syndrome characterized by a progressive decrease in the body's reserve and declining resistance to stressors, possibly because of declining capacity of multiple physiologic systems resulting in higher vulnerability morbidity and mortality. Ayurveda also mentions morbidity occurring with advancing age and various options for its management. Elixirs are recommended in Ayurveda, popularly called 'rasayana', for recovery from the symptoms of frailty. Worldwide, because of the wide demographic profile, the process of ageing exerts its effects on geriatric populations at different ages. Europeans were the first to paraphrase the word frailty for the ageing process. With better medical care and nutrition, a substantial subset of populations survives longer than 60 years or longer worldwide. The most relevant aspect of the recognition of syndrome of frailty is that the process is, to some extent, reversible, provided that adequate attention is paid and a timely intervention is performed for the needy subset of population, which is likely to improve the quality of life markedly, besides resulting in an increased life span.